Domestic Violence and its Maternal and Fetal Consequences Among Pregnant Women - Seyda Sobhani; Maryam Niknami; Seyedeh Noshaz Mirhaghjou; Zahra Atrkar Roshan (Journal of Holistic Nursing and Midwifery)
Introduction: Domestic violence is a global phenomenon which during pregnancy, not only affect mother s health, but can also directly or indirectly have an abusive effect on fetus s health. Objective: The objective of the present study is to determine the relationship between domestic violence during pregnancy with its consequences on pregnant women referring to public maternity hospitals of Rasht City, Iran. Materials and Methods: This research was a cross-sectional study of the descriptive analytical type, conducted on 402 pregnant women who referred to the state-owned maternity hospitals of Rasht City for childbirth in 2014. In this research, the study samples were collected through the convenient sampling method. Data collection tools were a questionnaire comprising of three parts; demographic information, WHO domestic violence during pregnancy questionnaire, and consequences in pregnancy, which were completed through interview with mothers. Finally, the obtained data were analyzed, through descriptive and inferential statistics conducted through the Chi-square test and multiple logistic regression. Results: Findings showed that 48.5% of pregnant women during their pregnancy had been subjected to domestic violence (the majority was emotional violence with 45.5% prevalence) by their spouses, and all aspects of violence have been reported with mild intensity. On determining the association between the experience of domestic violence during pregnancy and its effects on pregnancy, the Chi-square statistical test revealed statistically significant relationship between domestic violence and delivery method i.e., cesarean section (P=0.0001), vaginal bleeding (P=0.001), preterm labor (P=0.041), premature rupture of embryonic membranes (P=0.044) and low birth weight of neonates (˂2500 g) (P<0.0001). In the final model, of the main variables of the research, the emotional violence (OR=1.064, 95% CI=1.007-1.125, P=0.026) was the predictor of maternal and neonatal complications. Conclusion: Approximately, half of the women under the study were subject of domestic violence during their pregnancy, and considering its connection with the risk of maternal and neonatal complications, it is recommended that the proper interventions be planned to reduce domestic violence and its adverse consequences in pregnancy.